Contemporary clinical conversations about stuttering: Can intervention stop early stuttering development? - L. Edwards, Brooke; Jackson, Eric S.; Kefalianos, Elaina; Sheedy, Stacey; Onslow, Mark (International Journal of Speech-Language Pathology, 2025)
Purpose: To discuss whether early intervention can stop stuttering development. To inform junior clinicians and students of speech-language pathology about contemporary views on this issue. Method: The issue was discussed by two university researchers and two speech-language pathologists who provide public clinical services. Written conversational turns in an exchange were limited to 100 words each. When that written dialogue was concluded, each participant provided 200 words of final reflection about the issue. Result: Most differences that emerged centred on the clinical evidence base for early intervention, which emphasises stuttering reduction, and how it should be interpreted. Conclusion: The evidence base for early intervention has limitations and it should be interpreted cautiously. One interpretation is that reducing stuttering severity is a justifiable core of early management. Another interpretation focuses on ease of communication, anticipation of stuttering, and covert stuttering.